Arrhythmias in the congenital long QT syndrome: how often is torsade de pointes pause dependent?. Issue 6 (1st June 2000) - Viskin, S; Fish, R; Zeltser, D; Belhassen, B; Heller, K; Brosh, D; Laniado, S; Barron, H V
Abstract : OBJECTIVE: To determine the frequency and predictors of pause dependent torsade de pointes among patients with the congenital long QT syndrome and spontaneous ventricular tachyarrhythmias. DESIGN: The literature on the "congenital long QT" was reviewed. Articles with illustrations demonstrating the onset of spontaneous polymorphic ventricular arrhythmias in the absence of arrhythmogenic drugs were included. RESULTS: Illustrations of 62 spontaneous episodes of torsade de pointes among patients with congenital long QT syndrome were found in the literature. The majority (74%) of documented arrhythmias were "pause dependent"; 82% of these pauses were longer than the basic cycle length by > 100 ms. Age and sex correlated with the mode of arrhythmia initiation. Arrhythmias in infants (⩽ 3 years old) were not pause dependent, while female sex correlated with pause dependent torsade. Using multivariate analysis, age was the only independent predictor of the mode of onset of torsade de pointes. CONCLUSION: Available data suggest that the majority of spontaneous arrhythmias in the congenital long QT syndrome are pause dependent. Torsade de pointes that is not preceded by pauses appears to be limited to patient subgroups with severe forms of the disease, like symptomatic infants. These findings have important implications regarding the use of cardiac pacing for arrhythmia prevention.